PENILAIAN KEPATUHAN DAN EFEKTIVITAS PERATURAN ANTI PENCUCIAN UANG PADA INDONESIA EXIMBANK - Matthew Joshua Isarell (2021)
This Final Project Report is conducted at Indonesia Eximbank, which is located at Prosperity Tower, 1st Floor, District 8, SCBD Area, Lot 28, Jl. Jend. Sudirman No.Kav. 52-53, RT.8 / RW.3, Senayan, Kebayoran Baru, South Jakarta City, Jakarta 12190. Based on the idea that exports have an important role in spurring economic growth and refers to the existence of special institutions / institutions for export financing in many countries , then in 1999 the Government established PT Bank Export Indonesia (BEI). Given the importance of this institution, the establishment process also involved various government agencies and institutions, such as the Ministry of Finance, Ministry of Industry and Ministry of Trade, Office of the Coordinating Minister for Economic Affairs, BAPPENAS, Bank Indonesia and with full assistance from the Export Import Bank of Japan (Jexim). From a strategic and situational point of view at that time, the IDX was indispensable in supporting national export development efforts, one of which was in the form of continuing the developmental tasks of Bank Indonesia in supporting export financing, such as providing Export Liquidity Credits, Export Notes Rediscounts, FX Swaps, etc. . These tasks could no longer be performed by Bank Indonesia as a consequence of the provisions in the new Bank Indonesia Law.